Mapping global trends in labor income share studies - Diana Hassan; Assis Kamu; Nur Aliyah Jazuli; Ho Chung Mun (Human Resource Management Academic Research Society, 2025)
This study conducts a bibliometric analysis of global research on labor income share to identify key trends, influential authors and journals, and collaboration networks within the field. Using Scopus as the primary data source and analyzed through Bibliophagy tools, the study examines 95 documents published between 1988 and 2025, focusing on key themes such as labor income share and labor wage share, with all selected works limited to the English language. A notable increase in the number of annual publications was observed between 2020 and 2024, with a continued upward trend anticipated. The findings also reveal that research in this area is predominantly concentrated in developed economies, particularly China, with the Cambridge Journal of Economics having the highest local impact, evidenced by 182 citations. Additionally, the analysis highlights key research gaps, particularly regarding the influence of technological advancements, globalization, and energy dynamics on labor income share. These findings underscore the value of bibliometric analysis in mapping the scholarly landscape and providing a foundation for future research by identifying both areas of significant academic activity and those that remain underexplored.